Finance Leases: In the Shadow of Banks. (24th December 2021) - Chang, Jeffery (Jinfan); Yang, Ting; Shi, Yanping
Abstract: By analyzing a hand-collected transaction-level dataset on the finance leases of China's public firms for the period 2007–19, this article sheds light on China's leasing market, the second largest in the world. We find that banks use their affiliated leasing firms to provide credit to clients in order to circumvent the government's targeted credit tightening policy. In contrast to conventional view of regulatory arbitrage, our evidence shows that, rather than hiding risk and gambling for profit, banks-affiliated leasing firms have prudent risk control and efficient pricing. These bank-affiliated institutions are used by banks to play strategic role in relationship banking. Moreover, the ownership of the lessor also matters for the financing choice of the lessee.